Developing economies in the twenty-first century : the challenges of globalization - Yamazawa, Ippei (Institute of Developing Economies. Japan External Trade Organization ChibaJP, 2000)
Assess how to maximize the benefits and minimize the costs of globalization and the challenges ahead for China, Southeast Asia, India, Latin America, Africa and the Middle East.